TINGKAT PENGETAHUAN MASYARAKAT, PERSEPSI, DAN SIKAP TERHADAP KEHALALAN OBAT DI KECAMATAN CIOMAS - Noviyanto, Fajrin; Fadila, Lela; Insani, Nurul; Shobah, Afifah Nur; Ardianto, Teguh (Universitas Mathla’ul Anwar Banten, 2023)
This research aims to determine the level of knowledge, attitudes and perceptions of the community regarding halal medicine in Ciomas District. This research uses an observational descriptive approach model. The purposive sampling method was used to collect samples from the Muslim population of Ciomas District. To collect data, use a questionnaire. According to research results, 81% of residents of Ciomas District know about halal medicine. The public's perception of the halalness of medicines in Ciomas District has a score of 57%, and the attitude of the people of Ciomas District towards the halalness of medicines is higher with a score of 54%. So overall it can be concluded that the level of knowledge, perceptions and attitudes of the people of Ciomas District are in the very good category. Gender, age, education and occupation are components that influence people's knowledge, attitudes and perceptions about halal medicine in Ciomas District.